RALPH VAUGHAN WILLIAMS: “A CAMBRIDGE MASS”. ABOUT A NEWLY DISCOVERED MANUSCRIPT AND A WORLD PREMIERE, IN CONVERSATION WITH MAESTRO ALAN TONGUE - Bianca ŢIPLEA TEMEŞ (Studia Universitatis Babeş-Bolyai. Musica)
Acknowledged as one of the most prominent figures of British music history, the composer Ralph Vaughan Williams is well known to the world for pieces like Fantasia on a Theme of Thomas Tallis, A Sea Symphony, The Wasps and many others. Recently, the conductor Alan Tongue discovered at the Cambridge University Library a manuscript signed by Vaughan Williams: a Mass for soloists, choir and orchestra, written in 1899, with the academic purpose of obtaining the title of Doctor of Music. Professor Alan Tongue edited the score, conducted the premiere in London, on March 3rd, 2011, thus delivering a youthful masterpiece of the English composer to the international concert life.